A novel encryption algorithm for unstructured big data in wireless communication network. Issue 3 (4th April 2020) - Hou, Lixia; Ma, Chungeng; Yang, Lihui
In order to improve the confidentiality and security of transmission through data encryption, a novel encryption algorithm for unstructured big data in wireless communication network is proposed. In this algorithm, an encryption scheme of homomorphic public key is adopted to establish encryption key of unstructured big data, and an elliptic curve homomorphic encryption scheme is also adopted to design public key random number; the integral multiple bit length is adaptively adjusted to fixed-numbered public keys at different block lengths, and the random sampling method is adopted to extract features of encryption bit sequence, on which cyclic shift encryption is performed; encryption key and decryption key are established, and information entropy is adopted as a key sensitivity parameter concerning big data encryption to perform source coding to realise code element frequency detection of encryption output of unstructured big data, on which key padding is performed to optimise data encryption. Simulation results show that in unstructured big data encryption in wireless communication network, the proposed method can provide good confidentiality and steganography and relatively strong anti-attack capability.